Transcriptional and post-transcriptional regulation by sugar of the grape monosaccharide transporter VvHT1 - Agasse, A. (2005)
Poster apresentado no "IX Congresso Luso-Espanhol de Fisiologia Vegetal", em Évora, Portugal, em 2005.